Fixed-term contracts in EC countries - Ulrich Walwei (Intereconomics, 1991)
Since the beginning of the 1980s, an increase in the number of fixed-term employment contracts has been apparent in a number of free-market-oriented economies. This has been accompanied by amendments to the pertinent legislation. From the early to mid-1980s, a number of EC countries initiated legislation with the object of facilitating the conclusion of fixed-term contracts. How is this development to be assessed from an economic point of view?
Keywords: 330; European Community